2019
DOI: 10.1016/j.ijrmms.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the uniaxial compressive strength of extremely hard cryptocrystalline flint

Abstract: ReuseThis article is distributed under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs (CC BY-NC-ND) licence. This licence only allows you to download this work and share it with others as long as you credit the authors, but you can't change the article in any way or use it commercially. More information and the full terms of the licence here: https://creativecommons.org/licenses/ TakedownIf you consider content in White Rose Research Online to be in breach of UK law, please notify us by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…The hardness can be used to estimate the strength (e.g., UCS) of homogeneous vein-filling minerals (Grigg, 2016). Several experimental studies have demonstrated that hardness is lineally correlated with the yield strength and UCS of brittle, crystalline materials (Aliyu et al, 2019;Hucka & Das, 1974;ISRM, 1981;Kahraman et al, 2012;Zhang et al, 2011). It is noted that the yield strength of brittle, crystalline materials is approximately equal to the uniaxial tensile strength (Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hardness can be used to estimate the strength (e.g., UCS) of homogeneous vein-filling minerals (Grigg, 2016). Several experimental studies have demonstrated that hardness is lineally correlated with the yield strength and UCS of brittle, crystalline materials (Aliyu et al, 2019;Hucka & Das, 1974;ISRM, 1981;Kahraman et al, 2012;Zhang et al, 2011). It is noted that the yield strength of brittle, crystalline materials is approximately equal to the uniaxial tensile strength (Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Because the UCS values of rock-forming minerals are not available in the literature, instead, the hardness of mineral is frequently reported (Pellant, 2002). In addition, several experimental studies have demonstrated that hardness is lineally correlated with the UCS of brittle or crystalline materials (Aliyu et al, 2019;Grigg, 2016;Hucka & Das, 1974;ISRM, 1981;Kahraman et al, 2012;Zhang et al, 2011). The hardness was therefore used to estimate the UCS of the homogeneous vein-filling minerals (i.e., quartz and calcite), thus allowing the calibration of microparameters of the veins.…”
Section: 1029/2019jb019052mentioning
confidence: 99%
“…The accurate assessment of uniaxial compressive strength (UCS) is fundamental to rock mass classification and rock engineering design [1][2][3][4][5]. The conventional tests for UCS, however, have some shortcomings in that they are time-consuming and expensive and use restricted sampling.…”
Section: Introductionmentioning
confidence: 99%
“…The static rock elastic moduli are used to determine the formation strength parameters (UCS, friction angle, tensile strength), in situ stresses magnitudes, well completion design, reservoir subsidence modelling, borehole stability, wellbore breakouts characterization, fracture pressure prediction, anisotropy parameters and building a geomechanical model [11,15,17,18,35,36]. Even though it should be mentioned that for some rocks like flint [2], shear velocity showed no or poor correlation with their mechanical properties like UCS.…”
Section: Introductionmentioning
confidence: 99%
“…It should be highlighted that the shear velocity may also increases or decreases like the compressional velocity provided that shear weakening or shear strengthening take place, according to Eqs. (1) and (2).…”
Section: Introductionmentioning
confidence: 99%